The Influence of Social Media towards Students' Learning Results at Grade 7 MTSN 1 Kota Payakumbuh - Murni, Yenti; Hanani, Silfia; Sesmiarni, Zulfani; Efendi, Dedi; Eliwatis, Eliwatis (The Future of Education Journal, 2023)
This study aims to determine the impact of social media use on the academic achievement of grade 7 MTsN 1 students in Payakumbuh City. Qualitative research was used in this study. The data collection technique of this study is the literature review method, which is to record one of the information about student academic achievement, combine student test scores based on students' initial tests, public standards are used to review the information in this review. Research shows that social media use has a significant impact on poor academic performance. Based on preliminary surveys conducted by researchers, the results suggest that the use of social networks can affect students' academic performance. In addition, many factors affect student learning outcomes. This section can emerge from an external point of view and in the use of social media. Events that affect student academic achievement make social media an external variable. Fewer students regularly use social networks, which makes learning outcomes interesting and learning outcomes decrease